A Case of Dry Gangrene in an Autoimmune Patient: Diagnostic and Therapeutic Challenges - Pokhriyal, Parshant; Kumari, Muskan; Kharb, Damini; Gururani, Subodh; Nautiyal, Anuj (Indian Journal of Pharmacy Practice)
Dry gangrene is a severe complication of vascular insufficiency, often associated with Peripheral Arterial Disease (PAD), diabetes, or autoimmune conditions like Rheumatoid Arthritis (RA). This case report presents a patient with RA and PAD who developed dry gangrene, highlighting the diagnostic and therapeutic challenges in such cases. A 42-year-old female patient presented with fever, joint pain, bluish discoloration, and numbness in the extremities. The patient had a history of hypothyroidism and was previously treated for lower limb thrombosis. Physical examination revealed ischemic changes in the fingers and toes. Laboratory investigations showed elevated rheumatoid factor (74.4 IU/mL), high Anti-Cyclic Citrullinated Peptide (Anti-CCP) levels (>200 RU/mL), and positive Antinuclear Antibodies (ANA). Imaging confirmed peripheral arterial disease, and echocardiography suggested mild cardiac dysfunction. Management involved anticoagulation (apixaban), vasodilators (cilostazol, nifedipine, xantinol nicotinate), and antibiotics (clarithromycin, linezolid) to prevent secondary infections. Supportive therapy included analgesics and neuropathic pain management. The patient responded well to treatment and was discharged with counseling on limb care and lifestyle modifications. This case underscores the importance of early recognition and intervention in autoimmune-related vasculopathy leading to gangrene. A multidisciplinary approach, including rheumatology, vascular medicine, and cardiology, is essential for optimal patient outcomes. This report contributes to the understanding of vascular complications in RA and emphasizes the role of aggressive management in preventing severe ischemic events.
Keywords: Dry Gangrene; Rheumatoid Arthritis; Peripheral Arterial Disease; Vasculopathy; Autoimmune Disorder; Vascular Complications